PEMANFAATAN MINYAK JELANTAH SEBAGAI BIODIESEL: KAJIAN TEMPERATUR DAN WAKTU REAKSI TRANSESTERIFIKASI - Rhofita, Erry Ika (Fakultas Teknik Universitas Wisnuwardhana, 2016)
The production of biodiesel from waste cooking oil as an effort to reduce environmental pollution and it’s production cost . Free fatty acid content is high on used cooking oil is required twice in the biodiesel production process, namely the process of esterification and transesterification. The success is determined by the transesterification reaction temperature, reaction time, the rotation speed of the stirrer, the catalyst, the molar ratio of methanol, a type of alcohol, FFA content material; and the moisture content of materials. In this research study ditekannkan the transesterification process, especially changes in temperature (50oC, 55oC, 60oC, 65oC, and 70 oC) and time (30,60,90, and 120 minutes) to yield the amount of biodiesel. The results of GC-MS testing on used cooking oil is known that the content of lauric acid and palmitoleic acid contained in the raw material for biodiesel used cooking oil at 0% and 4.6 Wt% Wt, and FFA content of 9.67%. Transesterification optimal temperatures between 60oC to 65oC, capable mengahsilkan biodiesel yield of> 93%. Total yield of biodiesel produced in 30 minutes transesterification reached 80%, and 60 minutes to reach 90%.